2015
DOI: 10.7897/2230-8407.06672
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Phytochemical Screening, Renal and Haematological Effects of Portulaca Oleracea (Whole Plant) in Swiss Albino Mice

Abstract: Portulaca oleracea (Family Portulacaceae) has been used all over the world for its nutritional and medicinal properties. It shows a number of pharmacological activities but very little information is known about its toxicity profile. The present study was undertaken to find its acute and subacute oral toxicity. In acute oral toxicity, four doses 500mg,1000mg,1500mg and 2000mg/kg b.w were administered orally to swiss albino mice with the help of oral feeding needle. In subacute oral toxicity, the doses of 200mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The use of Portulaca oleracea in folk medicine dates back to ancient times. It has been listed by the World Health Organization (WHO) as one of the most commonly used medicinal plants, which has given it the name, 'Global Panacea' [6]. All parts of the plant, especially the leaves and stems, are useful as remedies for many ailments and they are usually used in fresh or dried state.…”
Section: Introductionmentioning
confidence: 99%
“…The use of Portulaca oleracea in folk medicine dates back to ancient times. It has been listed by the World Health Organization (WHO) as one of the most commonly used medicinal plants, which has given it the name, 'Global Panacea' [6]. All parts of the plant, especially the leaves and stems, are useful as remedies for many ailments and they are usually used in fresh or dried state.…”
Section: Introductionmentioning
confidence: 99%
“…Acute toxicity evaluation gives the information about LD50. Both subacute and chronic evaluations give information about the cumulative toxicity at low dose on prolonged period of time 11 . With this view, in the present study, the extract was subjected to a toxicity study.…”
Section: Discussionmentioning
confidence: 99%
“…The authors indicate that Moringa oleifera leaf extract has no toxic effects when administered in concentrated doses over a short period [170][171][172]. Hydroalcoholic extract of Portulaca oleracea at the dose level of 500 mg/kg can be used for further pharmacological activity and at the dose level of 400mg/kg have significant hepato protection [173]. The toxicity of compounds (phenolics, terpenoids and alkaloids) of certain anti-fatigue plants was also evaluated.The flavonoid fraction of the leaves of the Anisomelles Indica Kuntze seems to be safe for oral administration and has been shown that it is non-toxic following acute exhibitions with mice under experience conditions where the maximum tolerated dose is assessed at more than 5000 mg / kg B.W [63,174].…”
Section: Toxicity Of Doping Molecules and Herbalmentioning
confidence: 99%